Irregular Unions - Cleland, Katharine (Cornell University Press, 2021)
"Irregular Unions provides the first sustained literary history of clandestine marriage in early modern England. Augmenting recent literary and historical studies of marriage, the book constitutes an examination of the practice in a variety of poetic and dramatic genres." Provided by publisher.